Pengaruh Keselamatan Kesehatan Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan di Pelabuhan Teluk Bungus Padang - Putri, Rismadina Nauli; Salfadri, Salfadri; Meri Dwi Anggraeni (Fakultas Ekonomi, Universitas Ekasaktii, 2024)
A port is a place where ships stop to deliver goods or people. Teluk Bungus Padang Harbor is located on Jl Raya Padang - Painan KM 16 Padang, West Sumatra. Teluk Bungus Padang Harbor has 45 employees. This research aims to determine and analyze the influence of occupational safety and health and the work environment on employee performance at the port of Teluk Bungus Padang, both partially and simultaneously. The data collection method used in this research is field research and library research. The population used in this research was 44 people and the sample was 44 people. The data analysis method in this research uses multiple linear regression. The results of this research show that: 1) There is a positive and significant influence of occupational health safety on employee performance. 2) There is a positive and significant influence of the performance environment on employee performance. 3) There is a positive and significant influence on occupational safety and health and the work environment which simultaneously influences employee performance. The magnitude of the contribution of the influence of occupational safety and health and the work environment on employee performance at Teluk Bungus Padang port is 42.9%, while the remaining 57.1% is explained by other variables outside this research such as work motivation, work environment and others.